mpact of molecular weight of polyethylene glycol on physicochemical characteristics of polymeric nanoparticles encapsulating pimozide - HardipSinh Barad; Amal Ali Elkordy; Ahmed M Faheem (British Journal of Pharmacy, 2023)
The aim of the study is to examine the effect of the molecular weight of Polyethylene glycol (PEG) on the properties of nanoparticles. PEGlyation of nanoparticles is a promising approach to extend the circulation time and protect nanoparticles from opsonisation and macrophage. However, PEG molecular weight has a significant effect on key parameters of nanoparticles such as Size and encapsulation efficiency. In this study, PLGA-PEG nanoparticles with Pimozide were prepared using a microfluidic technique using two different molecular weights of PEG. Physicochemical characterizations were undertaken including Encapsulation efficiency and Fourier transform infrared spectroscopy (FTIR). Results were compared for these two formulations to understand how the weight variation of PEG impacts on physicochemical properties of nanoparticles.